The necessary and sufficient condition for the stability of a rigid body: Stability of a rigid body (JOURNAL OF ADVANCES IN PHYSICS, 2017)
In this paper, the stability of the unperturbed rigid body motion close to conditions, related with the center of mass, is investigated. The three first integrals for the equations of motion are obtained. These integrals are used to achieve a Lyapunov function and to obtain the necessary and sufficient condition satisfies the stability criteria.